2018
DOI: 10.2478/ctg-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

K-Mean Cluster Analysis for Better Determining the Sweet Spot Intervals of the Unconventional Organic-Rich Shale: A Case Study

Abstract: The petrophysical analysis is the crucial task for evaluating the quality of unconventional organic-rich shale and tight gas reservoirs. The presence of organic matter and the ultra-tight with over complex pore system have remained a lack of understanding of how to evaluate the extensive parameters of porosity considering organic content, gas saturation, organic richness, brittleness index, and sweet spot interval by only using conventional log. Therefore, this study offers effectively applied techniques and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Based on a literature study of similar previous studies, there are several advantages and disadvantages in each study that can be used as guidelines in this study. The research entitled K-Mean Cluster Analysis for Better Determining the Sweet Spot Intervals of the Unconventional Organic-Rich Shale: A Case Study by Akbar and Nugraha (2018) used the K-Mean Clustering method in classifying data from hydrocarbon exploration wells. This method is considered to be able to determine the desired number of clusters based on the number of parameters that depend on the distance between the data or the centroid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a literature study of similar previous studies, there are several advantages and disadvantages in each study that can be used as guidelines in this study. The research entitled K-Mean Cluster Analysis for Better Determining the Sweet Spot Intervals of the Unconventional Organic-Rich Shale: A Case Study by Akbar and Nugraha (2018) used the K-Mean Clustering method in classifying data from hydrocarbon exploration wells. This method is considered to be able to determine the desired number of clusters based on the number of parameters that depend on the distance between the data or the centroid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Altindag and Guney [14] presented some relationships to estimate brittleness based on UCS, Schmidt hardness number, and Ts. Akbar and Musu [15] studied the effect of mineralogy on the brittleness. Studies have revealed that MFFNN has high precision to estimate the Vs rock samples [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Samples in each class seem indistinguishable due to similar geological depositions and diagenetic alterations . Many methods have addressed rock typing, for example: Based on mechanical properties, mineralogy, and organic geochemistry The use of permeability, porosity, and irreducible water saturation data either empirically , or with a hydraulic flow unit (HFU) approach; ,, Involvement of capillary pressure data and J -function and combined with radius; Consideration of thin section descriptions and interpretations such as rock fabrics, depositional facies, and rock textures; , Geostatistics and machine learning implementation such as clustering, , ANN, self-organizing map, , and fuzzy logic; Grouping based on the dimensionless form of absolute permeability, relative permeability, porosity, and phase viscosity, the so-called true effective mobility TEM function; , The use of resistivity data and porosity to yield in electrical flow unit; Further development of analytical models, such as the pore geometry and structure (PGS) method. …”
Section: Introductionmentioning
confidence: 99%
“…Geostatistics and machine learning implementation such as clustering, , ANN, self-organizing map, , and fuzzy logic;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation